Paris-New York-Tokyo. (Tsubuka : Tsubuka Museum of Photography, 1985)
Misonne, Léonard ; Kertesz, André ; Brassaï ; Cartier-Bresson, Henri ; Doisneau, Robert ; Friedlander, Lee ; Davidson, Bruce ; Mapplethorpe, Robert ; Josephson, Ken ; Adams, Robert ; Gohlke, Frank ; Sternfeld, Joel ; Nakayama, Iwata ; Nakaji, Yasui ; Kuwabara, Kineo ; Kawada, Kikuji ; etc.
Paris-New York-Tokyo, Tsubuka Museum of Photography, Tsubuka, March 3 - September 16, 1985 ; Miyagi Museum of Art, Miyagi, November 9 - December 22, 1985
Japanese
kunstcatalogus
Keywords: Parijs; New York; Tokyo